Restored Immunosuppressive Effect of Mesenchymal Stem Cells on B Cells After Olfactory 1/Early B Cell Factor–Associated Zinc‐Finger Protein Down‐Regulation in Patients With Systemic Lupus Erythematosus. Issue 12 (December 2014) - Feng, Xuebing; Che, Nan; Liu, Yan; Chen, Haifeng; Wang, Dandan; Li, Xia; Chen, Weiwei; Ma, Xiaolei; Hua, Bingzhu; Gao, Xiang; Tsao, Betty P.; Sun, Lingyun
<x xml:space="preserve">Abstract</x> Objective To evaluate whether olfactory 1/early B cell factor–associated zinc‐finger protein (OAZ), a candidate lupus susceptibility gene involved in antinuclear antibody (ANA) production, plays a role in the regulation of B cells by mesenchymal stem cells (MSCs). Methods MSCs derived from the bone marrow of patients with systemic lupus erythematosus (SLE) and healthy control subjects were expanded and incubated with small interfering RNAs specific for OAZ or a nontargeting sequence. Knockdown of messenger RNA levels of OAZ and its downstream genes was measured using real‐time polymerase chain reaction, and protein levels of chemokine/cytokine and immunoglobulins were determined by enzyme‐linked immunosorbent assay or Western blotting. The effects of modulating the OAZ levels in MSCs, by either silencing or overexpression, on B cell proliferation and terminal differentiation were assessed by coculturing MSCs with mouse spleen cells. Results OAZ gene expression was highly enriched in MSCs compared with peripheral blood leukocytes and was increased in patients with SLE compared with control subjects. After the silencing of OAZ expression, SLE MSCs could regain the ability to inhibit B cell proliferation and terminal differentiation, as indicated by decreased percentages of bromodeoxyuridine‐positive cells and CD138+ cells as well as decreased levels of IgG, IgM, and ANAs. The level of CCL2 was increased after OAZ knockdown, while anti‐CCL2 antibodies completely counteracted the effect of OAZ silencing. Umbilical cord–derived normal MSCs that overexpressed OAZ had a diminished ability to inhibit B cell proliferation and terminal differentiation. Conclusion OAZ down‐regulation could restore the impaired function of SLE MSCs in the immune regulation of B cells, contributing to a reduction in ANA levels. OAZ might represent a new target for therapy in patients with SLE.